2017
DOI: 10.1249/mss.0000000000001111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry Needling on Thigh Muscle Strength and Hip Flexion in Elite Soccer Players

Abstract: DN showed a significant effect on muscular endurance and hip flexion range of motion that persisted 4 wk posttreatment. Compared with placebo, it showed a significant effect on hip flexion that persisted 4 wk posttreatment, and compared with nonintervention control, it showed a significant effect on maximum force of knee extensors 4 wk posttreatment in elite soccer players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 27 publications
1
46
0
1
Order By: Relevance
“…Haser et al 7 found that dry needling increased maximal force in knee extensor muscles, but this current study is the first to examine the effects that dry needling has on a functional activity such as vertical jump. Vertical jump is a functional activity that can be conducted as a proxy measure of the gastrocnemius/soleus muscle complex performance.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Haser et al 7 found that dry needling increased maximal force in knee extensor muscles, but this current study is the first to examine the effects that dry needling has on a functional activity such as vertical jump. Vertical jump is a functional activity that can be conducted as a proxy measure of the gastrocnemius/soleus muscle complex performance.…”
Section: Discussionmentioning
confidence: 81%
“…5 Dry needling combined with physical therapy has been found to reduce pain and increase range of motion and function in subjects suffering from chronic pain following a total knee arthroplasty. 6 Haser et al 7 investigated the treatment of chronic ankle sprains in soccer players and found dry needling to be an effective adjunct to proprioceptive and strengthening exercises for the management of chronic ankle sprains. In addition, Haser et al 7 reported that dry needling increased maximal force output of the quadriceps muscles and decreased injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dry needling (DN) is used to treat musculoskeletal injuries, pain, and muscle tension reduction [29][30][31]. Most of the current literature has shown the effectiveness of DN on latent trigger points [32][33][34], but there has also been success in its use to increase range of motion (ROM) after a muscle strain [35] and after an ACL reconstruction [30]. Myofascial pain is a common form of pain that arises from muscles or related fascia and is usually associated with myofascial trigger points (MTrP) and musculoskeletal injuries [33].…”
Section: Hivamat and Theragun Are Two Varieties Of Handheld Vibrationmentioning
confidence: 99%
“…This form of intervention has seen good results in the treatment of MTrPs [33,34,44]. In addition to focusing on MTrPs within a muscle to release tension, there have also been studies that focus on MTrPs to increase ROM, short-term muscle endurance, and return to performance in elite athletes [45]. Most importantly, DN can help with the management of rotator cuff, as part of a conservative therapeutic intervention plan instead of surgical intervention [31].…”
Section: Hivamat and Theragun Are Two Varieties Of Handheld Vibrationmentioning
confidence: 99%